PERLINDUNGAN DAN PENEGAKKAN HUKUM BAGI PELAKU DAN KORBAN PERUNDUNGAN ( BULLYING) - La Ode , Bunga Ali; Herdin, Herdin (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2025)
This study aims to examine how the law is enforced against perpetrators of bullying in Indonesia, and how legal protection is provided to both victims and perpetrators. The research uses a normative method with a statutory and restorative justice approach, especially concerning children as both offenders and victims. The results show that law enforcement is carried out in stages, from reporting and investigation to possible resolution through mediation or juvenile justice proceedings. Legal protection is provided under the Child Protection Law and the Witness and Victim Protection Law, which guarantee safety, identity confidentiality, psychological assistance, and rehabilitation. Bullying management should ideally be handled collaboratively among the police, psychologists, and educational institutions, using an approach that emphasizes recovery rather than retribution.